2013
DOI: 10.1038/bjc.2013.547
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implication of SS18 -SSX fusion gene in synovial sarcoma

Abstract: Background:The aim of this study is to evaluate distribution and clinical impact of the SS18-SSX fusion gene in patients with synovial sarcoma in China.Methods:We collected and analysed the clinical data of 88 patients using univariate and multivariate survival analysis. HEK 293T and NIH 3T3 cell lines were transfected with the SS18-SSX1 or SS18-SSX2 gene to determine the respective involvement of these fusion genes in cell proliferation and invasion.Results:Overall survival was significantly better among SS18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The smaller the tumors the more favorable patient's outcomes. Also in previous studies smaller tumors were associated with more favorable outcome.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The smaller the tumors the more favorable patient's outcomes. Also in previous studies smaller tumors were associated with more favorable outcome.…”
Section: Discussionmentioning
confidence: 61%
“…Some authors described histological grade G3 (FNCLCC) to be associated with adverse outcome . In the multivariate analysis of patients (4–82 years of age) by Guillou et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to make a definite diagnosis of SS even with histopathology. But immunohistochemistry and identification of SYT/SSX fusion transcript are useful for confirmation 6. Chemotherapy and radiotherapy are common therapy regimes for metastatic SS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of 141 patients by Guillou et al [13] did not show any correlation between fusion protein status and survival. Recently, the association of SSX1 tumors with worse OS was found to be statistically significant in a Chinese study of 88 patients (P < 0.001), with additional cell line experiments showing significantly more proliferative and invasive characteristics when transfected with the SS18-SSX1 compared with the SS18-SSX2 gene [14]. Interestingly, the monophasic subtype is thought to be related to the SSX2 translocation, whereas SSX1 tumors are thought to be linked to a biphasic phenotype, implicating worse prognosis for patients with biphasic tumors [5].…”
Section: Predicting Tumor Behaviormentioning
confidence: 99%
“…In contrast to the usually early development of metastases in STS in general, a long followup study of 62 patients with synovial sarcoma reported local recurrence and metastases after a mean of 3.6 (range 0.5-15) and 5.7 years (range 0. [5][6][7][8][9][10][11][12][13][14][15][16], respectively [8].…”
Section: Introductionmentioning
confidence: 99%